Contribution of Phenolics and Free Amino Acids on the Antioxidant Profile of Commercial Lemon Verbena Infusions - Juliana A. Barreto Peixoto; Gerardo Álvarez-Rivera; Anabela S. G. Costa; Susana Machado; Alejandro Cifuentes; Elena Ibáñez; M. Beatriz P. P. Oliveira; Rita C. Alves (MDPI AG, 2023)
Lemon verbena infusions are widely appreciated due to their agreeable lemony flavor and medicinal properties. In this study, the antioxidant potential, phenolic profile, and free amino acid profile of lemon verbena infusions from different commercial brands were studied. Characterization by UHPLC-QTOF-HRMS allowed the identification of 34 phenolics. The free amino acid profile (by RP-HPLC-FLD) was assessed for the first time, allowing the quantification of 16 amino acids. Furthermore, the infusions showed high antioxidant activity by different assays (ferric reducing antioxidant power, DPPH• scavenging, and oxygen radical absorbance capacity assays), which in turn were significantly correlated with total phenolics and total flavonoid contents. Notwithstanding, phenylalanine seemed to have also an impact on the antioxidant activity of the infusions, with significant correlations found. Finally, significant differences were found in all the evaluated parameters for one of the four commercial brands herein studied, which was possibly related to the different geographical origins of this sample. Overall, these lemon verbena infusions proved to be rich in a huge variety of bioactive compounds that can provide therapeutic potential.